The Development of Adolescents' Self-concept of Ability through Grades 7-9 and the Role of Parental Beliefs - Laura Annukka Pesu; Kaisa Aunola; Jaana Viljaranta; Jari-Erik Nurmi (EARLI, 2016)
This study examined the development of adolescents' self-concept of ability in math and literacy during secondary school, and the role that mothers' and fathers' beliefs concerning their child's abilities play in this development. Also examined was whether the role of mothers' and fathers' beliefs about their adolescent child's ability in math and literacy differs according to the adolescent's gender and level of performance. A total of 231 adolescents and their mothers and fathers were followed up across secondary school. The results showed, first, that adolescents' self-concept of ability declined slightly from grade 7 to grade 9 in both math and literacy. Second, mothers' and fathers' beliefs about their adolescent child's abilities in grade 7 predicted the child's subsequent self-concept in grade 9, but only in math.  Third, the role of mothers' beliefs in their child's self-concept of math ability was found to be stronger among high-performing than low-performing adolescents.